p100 increases AT1R expression through interaction with AT1R 3′-UTR - Paukku, Kirsi (Oxford University Press, 2008)
p100 protein (SND1, Tudor-SN) is a multifunctional protein that functions as a co-activator for several transcription factors, has a role in mRNA processing and participates in RNAi-induced silencing complex (RISC) with yet unknown function. In this study we identified a novel function for p100 as a regulator of angiotensin II type 1 receptor (AT1R) expression. The binding of p100 to AT1R 3′-untranslated region (3′-UTR) via staphylococcal nuclease-like (SN-like) domains increased receptor expression by decreasing the rate of mRNA decay and enhancing its translation. Overexpression of p100 increased AT1R expression, whereas decrease in p100 binding to 3′-UTR either by p100 silencing or by the deletion of p100 binding site downregulated receptor expression. The effect of p100 through AT1R 3′-UTR was independent of Argonaute2 (Ago2), a known p100 partner, and was thus RISC-independent. Nucleotides 118 to 120 of the AT1R 3′-UTR were found to be critical for the binding of p100 to 3′-UTR. In summary, p100 is a multifunctional regulator of gene expression that regulates transcription, mRNA maturation, and as described in this article, also mRNA stability and translation.